Efficacy and safety of platelet-rich plasma in the treatment of carpal tunnel syndrome: A network meta-analysis of different injection treatments - Hong, Pan; Zheng, Yu; Rai, Saroj; Ding, Yuhong; Zhou, Yeming; Liu, Ruikang; Li, Jin (Frontiers in Pharmacology, 2022)
Purpose: Carpal tunnel syndrome (CTS) is a common form of median nerve compression in the wrist caused by focal peripheral neuropathy. Platelet-rich plasma (PRP) therapy could improve healing ability by exposing injured tissues to high concentrations of autologous growth factors. Our study aims to compare all injective treatments for CTS, and assessed the efficacy and priority of PRP therapy. Methods: We searched Medline, Embase, Web of Science, Cochrane databases and Clinicaltrial.gov until Sep 19th, 2022. We only included data from randomized controlled trials (RCTs) which evaluated PRP injection therapy or drug injection therapy. Included RCTs measured at least one of the following three outcomes with validated instruments: in visual analogue scale (VAS), symptom severity scale (SSS) and functional status scale (FSS). Results: Overall, 19 studies with 1066 patients were included in this study. We used the SUCRA rankings to determine the merits of various therapies. In all, 5% dextrose injections were the best treatment strategy for VAS (MD -1.22, 95%CI -2.66 to 0.23; SUCRA=79.2%), followed by triamcinolone (high-dose) injections (MD -0.69, 95%CI -2.11 to 0.73; SUCRA=62.7%) and PRP injections (MD -0.39, 95%CI -1.67 to 0.89; SUCRA=60.0%). In SSS, the most effective intervention was hydroxy progesterone injections (MD -0.62, 95%CI -1.09 to -0.16; SUCRA=91.0%). The SUCRA ranking of PRP was second only to steroids and estrogen (MD -0.39, 95%CI -0.60 to -0.18; SUCRA=60.8%). In FSS, the best regimen strategy was hydroxy progesterone injections (MD 0.12, 95%CI -0.30 to 0.54; SUCRA=99.5%), followed by triamcinolone (little-dose) injections (MD -0.02, 95%CI -0.54 to 0.49; SUCRA=87.4%) and PRP injections (MD -0.26, 95%CI -0.43 to -0.09; SUCRA=77.1%). Conclusion: PRP is an alternative choice for CTS. PRP injection is second only to steroids and estrogen in the treatment efficacy of CTS, with wide indication and safe outcome.